A new species of Phrynopus from the northeastern Andes of Peru, its phylogenetic position, and notes on the relationships of Holoadeninae (Anura: Craugastoridae) - Venegas, Pablo J.; Barboza, Andy C.; Riva, Ignacio De La; Padial, José M. (Zootaxa, 2018)
We report the discovery of a geographically disjunct and morphologically distinctive species of direct-developing frog of the genus Phrynopus (Phrynopus mariellaleo sp. nov.) that changes considerably our understanding of the distribution of species in this Andean genus. The type locality lies on a subcordillera (Cerro de Campanario area) of the extreme northeastern portion of the Cordillera Central of Peru, on the headwaters of the Mayo River, Amazonas department, at 2575 m asl (6°6’42.9’’S, 77°26’24’’W). This area is situated 170 km to the NE from the northernmost record of Phrynopus known so far. Molecular phylogenetic analyses of a supermatrix (13269 aligned positions of gene sequences of four mitochondrial and ten nuclear genes) of 105 terminals (representing 93 named and 9 unnamed species of Holoadeninae) recover this new species as the sister to Phrynopus auriculatus, a species occurring more than 500 km south of the type locality of the new species. Both Phrynopus auriculatus and the new species occur at moderate elevations on the easternmost stretches of the Andean subcordilleras; their sister relationship point to a potentially broader distribution of species of Phrynopus along the poorly sampled intervening areas of the eastern hills of the Andes. The new species has a conspicuous and visibly large tympanic membrane (a trait rare in the clade), outlined by a marked bold black supratympanic fold and a black facial mask, and exhibits conspicuous dorsolateral, scapular, and middorsal Y-shaped folds. Specimens were found on the forest floor—a rocky substrate covered by a thick layer of leaf litter, moss and roots—of a primary humid montane forest (Yungas ecoregion) with scattered patches of bamboo (Chusquea spp.). Our phylogenetic analyses corroborate the monophyly of all Holoadeninae genera, including Euparkerella and Psychrophrynella, genera for which tests of monophyly were pending, and corroborates Hypodactylus nigrovittatus as part of Hypodactylus and sister to a clade that includes H. brunneus, H. elassodiscus and H. peraccai.